2020
DOI: 10.1108/acmm-02-2020-2262
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical corrosion behavior of type 444 stainless steel in synthetic tap water at different temperatures

Abstract: Purpose The purpose of this paper is to investigate the electrochemical corrosion behavior of type 444 stainless steel (SS) in synthetic tap water from 25°C to 80°C, i.e. the operation environment of the electric water heater. Design/methodology/approach The corrosion behavior was studied by using electrochemical measurements such as electrochemical impedance spectroscopy and polarization curve. The specimen surfaces were observed with scanning electron microscopy. The passive films were characterized with X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…E pit is the potential matching with the position where the current density increases rapidly on the anodic polarization curve, that is, the position where the passivation zone (where current does not change with potential) ends . In other words, E pit is determined by the breakdown of the passivation coating . The higher the E pit , the larger the width of the passivation region, and the better the pitting resistance of alloys .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…E pit is the potential matching with the position where the current density increases rapidly on the anodic polarization curve, that is, the position where the passivation zone (where current does not change with potential) ends . In other words, E pit is determined by the breakdown of the passivation coating . The higher the E pit , the larger the width of the passivation region, and the better the pitting resistance of alloys .…”
Section: Resultsmentioning
confidence: 99%
“…39 In other words, E pit is determined by the breakdown of the passivation coating. 40 The higher the E pit , the larger the width of the passivation region, and the better the pitting resistance of alloys. 41 The HTC2 coating had the lowest i corr and a passivation region of about 500 mV, indicating that with the appropriate amount of CuO doped TiO 2 coating Mg alloy corrosion could be effectually avoided.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This can be mainly attributed to the significant reduction in oxygen content in the solution. It is reported that the dissolved oxygen content linearly changes from about 8.0 to 3.5 mg L −1 with the increase in temperature from 25 to 80 • C [27], which is unfavorable for the cathodic reaction of the corrosion process.…”
Section: Corrosion Mechanism Under Different Temperaturesmentioning
confidence: 99%
“…The pitting resistance becomes higher under higher HCO 3 − and SO 4 2− concentrations in the solution [16,17]. Zhang [18] and Niu [19] studied the effect of Cl − and SO 4 2− ions on the pitting corrosion behavior of stainless steel in synthetic tap water. They found that there was a critical Cl − concentration for the occurrence of pitting corrosion and the pitting potential decreased significantly with the increase of Cl − concentration.…”
Section: Introductionmentioning
confidence: 99%